Incidence of neonatal hypothermia at birth in hospitals of Islamic Republic of Iran: A review - Roya Farhadi; Mohammad Sadegh Rezai; Maryam Nakhshab (Mazandaran University of Medical Sciences, 2014)
Hypothermia is an important cause of neonatal morbidity and mortality especially in low-income settings. To control this problem in countries such as Iran a full knowledge of the situation is of great importance. A review was performed both in Persian and English, including international databases. Totally 934 articles were reviewed and finally five articles were selected. The incidence of neonatal hypothermia in different parts of Iran was reported between 7.48 to 53.3 percent. The prevalence of neonatal hypothermia is a matter of concern and further studies are needed to determine this prevalence in all parts of Iran. Furthermore, performing more etiological investigations are recommended.